Flowing-water optical power meter for primary-standard, multi-kilowatt laser power measurements*This work of the U.S. Government is not subject to U.S. copyright. (9th May 2018) - Williams, P A; Hadler, J A; Cromer, C; West, J; Li, X; Lehman, J H
Abstract: A primary-standard flowing-water optical power meter for measuring multi-kilowatt laser emission has been built and operated. The design and operational details of this primary standard are described, and a full uncertainty analysis is provided covering the measurement range from 1–10 kW with an expanded uncertainty of 1.2%. Validating measurements at 5 kW and 10 kW show agreement with other measurement techniques to within the measurement uncertainty.